2021
DOI: 10.29219/fnr.v65.5490
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of meal tolerance test and oral glucose tolerance test for predicting insulin therapy in patients with gestational diabetes

Abstract: Aims: To identify factors predicting a need for insulin therapy in gestational diabetes mellitus (GDM) by comparing plasma glucose (PG) levels in a 75-g oral glucose tolerance test (75-g OGTT) with those in a 500-kcal meal tolerance test (MTT) containing 75 g of carbohydrate. Subjects and methods: The MTT was performed in 61 patients who diagnosed with GDM by a 75-g OGTT (age, 33.2 ± 4.5 years; prepregnancy body mass index, 22.6 ± 4.7 kg/m2; number of gestational weeks, 25.1 ± 6.4 weeks). PG and serum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…We could not analyze pre-conceptional BMI or serum insulin levels during OGTT. We found that higher HbA1c levels at the diagnosis predicted insulin requirement in GDM, similarly in the previous studies 33 36 . Actually, an increased HbA1c level may already be expected to be an important determinant of insulin use in a pregnant woman with GDM.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We could not analyze pre-conceptional BMI or serum insulin levels during OGTT. We found that higher HbA1c levels at the diagnosis predicted insulin requirement in GDM, similarly in the previous studies 33 36 . Actually, an increased HbA1c level may already be expected to be an important determinant of insulin use in a pregnant woman with GDM.…”
Section: Discussionsupporting
confidence: 90%
“…Maternal age, previous history of GDM, family history of type 2 diabetes mellitus, pre-conceptional body mass index, FBG, 1st-hour or 2nd-hour glucose level on OGTT, and HbA1c were found as predictors for insulin use in GDM 32 33 34 . In the other studies, the gestational week at the time of the diagnosis of GDM, abdominal subcutaneous fat thickness, and HOMA-IR were associated with insulin treatment in GDM 34 35 36 . IMH was not analyzed as a predictor for insulin use in GDM in any previous study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The nutritional intake during MTT is more balanced than that during OGTT. Therefore, MTT accurately detects the effects of functional components in models of insulin resistance [ 54 , 55 ]. As humans spend most of their time after eating, observing the course of glucose regulation after MTT is more interesting than observing fasting glucose concentration.…”
Section: Discussionmentioning
confidence: 99%
“…IGI is also used in the case of meal tolerance test (MTT) [23]. Comparison study with GTT and MTT was found [24]. Authors et al investigated IRI and Cpeptide responses for MTT [25,18].…”
Section: Discussionmentioning
confidence: 99%